2019
DOI: 10.1186/s12967-019-2093-y
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of microRNA-130 family expression in patients with cancer: a meta-analysis and database test

Abstract: BackgroundEmerging evidence shows that microRNA-130 (miRNA-130) family may be useful as prognostic biomarkers in cancer. However, there is no confirmation in an independent validation study. The aim of this study was to summarize the prognostic value of miRNA-130 family (miRNA-130a and miRNA-130b) for survival in patients with cancer.MethodsThe pooled hazard ratios (HRs) with 95% confidence intervals (CIs) were calculated to estimate the association strength between miRNA-130 family expression and prognosis. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
0
9
0
3
Order By: Relevance
“…Differences in miR expression have not only been described in tissue biopsies, but also in blood samples of cancer patients [ 48 , 59 ]. As in tissues, some miRs have been proposed as potential blood biomarkers for cancer diagnosis and prognosis [ 60 , 61 , 62 , 63 ]. Previous studies have proposed using miR-145 as a biomarker of ovarian cancer because miR-145 serum levels are significantly down-regulated in patients with ovarian cancer and benign ovarian tumors, compared to healthy controls [ 38 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in miR expression have not only been described in tissue biopsies, but also in blood samples of cancer patients [ 48 , 59 ]. As in tissues, some miRs have been proposed as potential blood biomarkers for cancer diagnosis and prognosis [ 60 , 61 , 62 , 63 ]. Previous studies have proposed using miR-145 as a biomarker of ovarian cancer because miR-145 serum levels are significantly down-regulated in patients with ovarian cancer and benign ovarian tumors, compared to healthy controls [ 38 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacological inhibition of miR-130 family molecules by seed-targeting with an 8-mer tiny locked nucleic acid (LNA) inhibited bladder cancer cell growth, migration, and invasion by repressing stress fiber formation ( 173 ). Overall, miRNA-130 is highly expressed in patients with different types of cancer and is correlated with severe tumors and poor cancer prognosis ( 174 ).…”
Section: The Role Of Adipose Tissue Mirnas In Cancermentioning
confidence: 99%
“…Contrastingly, Kaplan-Meier analysis by Li B et al demonstrated that high expression of miR-130a in patients with hepatocellular carcinoma (HCC) had significantly improved OS [23]. In a recent meta-analysis, Peng et al evaluated 12 eligible studies comprising 1582 cases with various types of cancer, including HCC, colorectal cancer, gastric cancer, lymphoma, non-small-cell lung cancer, cervical cancer, cholangiocarcinoma, and osteosarcoma, and the pooled Journal of Oncology hazard ratios (HRs) indicated a significant relationship between the high levels of miR-130a expression and poor OS in cancer patients (HR � 1.58, 95%CI � 1.21-2.06, p < 0.001) [39]. Up to now, the prognostic role of miR-130a has not been investigated in OSCC.…”
Section: Discussionmentioning
confidence: 99%